Telemedicine in Pediatric Intensive Care Units: Perspectives From a Brazilian Experience - Jacovas, Vanessa Cristina (Curr Pediatr Rep, 2021)
PURPOSE OF REVIEW: To present the implementation of a telemedicine project (TeleICU) in pediatric intensive care units (ICU) throughout different Brazilian regions. RECENT FINDINGS: Although telemedicine in pediatric ICUs has shown evidence of benefit in numerous studies with potential to 18 mitigate existing disparities, in Brazil, its use is still under development. Brazil has several opportunities for implementing this resource since, according to the National Registry of Healthcare 20 Establishments (NRHE), there is a discrepancy in the density of pediatric intensive care physicians per patient and the availability 21 of pediatric ICU beds per number of inhabitants. SUMMARY: Health technologies are being widely used to fill gaps in the healthcare system. Telemedicine has been an important tool to meet demands in intensive care units, especially the demand for specialized assistance. TeleICU is a Brazilian model of telemedicine that performs multidisciplinary telerounds in remote pediatric ICUs and develops continuing education activities for the healthcare teams. The project aims to systematize and to qualify care, as well as to reduce risks for patients admitted to pediatric ICUs engaged in the project. Preliminary results have demonstrated a positive impact regarding this approach, providing medical care to 6640 inpatients-day in two Brazilian pediatric ICUs, for 616 patients during 946 daily telerounds. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40124-021-00242-z.